Development of Sensitive and Rapid RNA Transcription-based Isothermal Amplification Method for Detection of Mycobacterium tuberculosis - Ramezani, Reihaneh (Avicenna J Med Biotechnol, 2019)
BACKGROUND: The accurate and early diagnosis of tuberculosis is important for its effective management. During the last decade, several molecular methods for detection of Tuberculosis (TB) have been developed. Since RNA especially mRNA has a generally much shorter half-life than DNA, its detection may be useful for the assessment of viability of bacteria. This research is a Nucleic Acid Sequence Based Amplification-Enzyme Linked Immunosorbent Assay (NASBA-ELISA) which was designed and developed for rapid detection of viable Mycobacterium tuberculosis (M. tuberculosis). METHODS: Oligonucleotide primers targeting tuf gene encoding viability marker EF-Tu mRNAs were selected and used for the amplification of mycobacterial RNA by the isothermal NASBA Digoxigenin (DIG) labeling process and incorporated with DIG-UTP, reverse transcriptase and T7 RNA polymerase. RESULTS: Using the NASBA-ELISA system, as little as 17.5 pg of RNA of M. tuberculosis was detected within 4 hr and no interference was encountered in the amplification and detection of viable M. tuberculosis in the presence of non-target RNA or DNA. Results obtained from the clinical specimens showed 97 and 75% of sensitivity and specificity, respectively. CONCLUSION: The NASBA-ELISA system offers several advantages in terms of sensitivity, rapidity and simplicity for detection of M. tuberculosis. Furthermore, due to its simplicity and high sensitivity feature, it could be used in limited access laboratories in a cost-effective manner.